Predictors of Successful Clinical and Laboratory Outcomes in Patients with Primary Sclerosing Cholangitis Undergoing Endoscopic Retrograde Cholangiopancreatography - R Enns; MA Eloubeidi; K Mergener; PS Jowell; MS Branch; J Baillie (Canadian Journal of Gastroenterology)
Endoscopic retrograde cholangiopancreatography (ERCP) in patients with primary sclerosing cholangitis (PSC) can be a challenging and sometimes gratifying opportunity for therapeutic intervention. Although there often appears to be initial radiological improvement after ERCP, the benefit as measured by serial estimations of subsequent liver enzymes is questionable. The fluctuating course of the inflammatory process makes the interpretation of serology even more difficult.